2018
DOI: 10.9734/ajpas/2018/v1i324532
|View full text |Cite
|
Sign up to set email alerts
|

The Kumaraswamy Exponentiated U-Quadratic Distribution: Properties and Application

Abstract: In this paper, a new lifetime model called Kumaraswamy exponentiated U-quadratic (KwEUq) distribution is proposed. Several mathematical and statistical properties are derived and studied such as the explicit form of the quantile function, moments, moment generating function, order statistics, probability weighted moments, Shannon entropy and Renyi entropy. We also found that the usual maximum likelihood estimates (MLEs) fail to hold for the KwEUq distribution. Two alternative methods are suggested for the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…The existence of the MLEs under some possible conditions are discussed below. Similar studies can be found in [32], [42]- [47].…”
Section: ) Maximum Likelihood Methodssupporting
confidence: 87%
“…The existence of the MLEs under some possible conditions are discussed below. Similar studies can be found in [32], [42]- [47].…”
Section: ) Maximum Likelihood Methodssupporting
confidence: 87%
“…Thus, little foliage loss occurs during the early stages of development. Once the fourth instar is attained, larvae can do considerable damage by severing young plants, and a larva may cut several plants in a single night [1]. Cutworm is nocturnal as it attacks the young seedling of the plants at night.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized inverted K-G Physics data [72] Topp-Leone generalized inverted K model Physics data [73] K log-logistic Weibull model Failure times data [74] Exponentiated inverse K model Economic data [75] Beta K Burr Type X model Physics and medical data [76] Marshall-Olkin extended inverted K model Physics, failure and medical data [77] K generalized Kappa model Geological data [78] Cubic rank transmuted K model Food and industrial data [79] K Marshall-Olkin log-logistic model Physics data [67] Odd generalized exponential K model Geological and environmental data [80] K exponentiated U-quadratic model Medical data [81] K odd Burr-G Physics and engineering data [82] Exponentiated generalized K model Environmental, agriculture and engineering data [83] Size-biased K model Engineering data [84] K generalized power Weibull model Engineering data [85] Exponentiated K-Dagum model Income and lifetime data [61]…”
Section: Model Modeling Authorsmentioning
confidence: 99%